Tooth loss and need for prosthetic treatment. El Carmen, Barinas State, Venezuela, 2018 - Yoel Gonzalez Beriau; Nadia Jover Capote (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: Tooth decay and periodontal disease are currently considered the main causes of tooth loss. Timely prosthetic rehabilitation is the ideal treatment for this problem, as it allows the restoration of lost functions. Objective: to characterize tooth loss in relation to the need for prosthetic treatment. Methods: descriptive, observational, cross-sectional study, carried out with all the patients who attended the El Carmen stomatological consultation, belonging to the Barrio Adentro Mission in the Barinas, Venezuela, from January to June 2018. The age, tooth loss, need for prosthetic treatment and type of prosthesis were analyzed. Results: female sex predominated, represented by 62.4%, and patients aged between 19 and 34 years old, with 48.7%. The loss of 7 and more teeth prevailed in the studied group. The 63.4% required prosthetic treatment, and partial rehabilitation was the most demanded. Conclusion: the conditions of oral health, specifically of tooth loss, in these Venezuelan patients, were characterized by the predominance of the female sex, as well as the youngest. A large number of participants were affected by the absence of seven and more teeth. The need for prosthetic treatment increased with age, with a greater demand for partial prostheses.